Effect of an acute moderate-exercise session on metabolic and inflammatory profile of PPAR- knockout mice - Silveira, Loreana S. [UNESP]; Pimentel, Gustavo D.; Souza, Camila O.; Biondo, Luana A.; Teixeira, Alexandre Abilio S.; Lima, Edson A.; Batatinha, Helena A. P.; Rosa Neto, Jose C.; Lira, Fabio S. [UNESP] (Wiley-Blackwell, 2017)
Peroxisome proliferator-activated receptors (PPARs) play a major role in metabolism and inflammatory control. Exercise can modulate PPAR expression in skeletal muscle, adipose tissue, and macrophages. Little is known about the effects of PPAR- in metabolic profile and cytokine secretion after acute exercise in macrophages. In this context, the aim of this study was to understand the influence of PPAR- on exercise-mediated immune metabolic parameters in peritoneal macrophages. Mice C57BL/6 (WT) and PPAR- knockout (KO) were examined in non-exercising control (n=4) or 24hours after acute moderate exercise (n=8). Metabolic parameters (glucose, non-esterified fatty acids, total cholesterol [TC], and triacylglycerol [TG]) were assessed in serum. Cytokine concentrations (IL-1, IL-6, IL-10, TNF-, and MCP-1) were measured from peritoneal macrophages cultured or not with LPS (2.5g/mL) and Rosiglitazone (1M). Exercised KO mice exhibited low glucose concentration and higher TC and TG in serum. At baseline, no difference in cytokine production between the genotypes was observed. However, IL-1 was significantly higher in KO mice after LPS stimulus. IL-6 and IL-1 had increased concentrations in KO compared with WT, even after exercise. MCP-1 was not restored in exercised KO LPS group. Rosiglitazone was not able to reduce proinflammatory cytokine production in KO mice at baseline level or associated with exercise. Acute exercise did not alter mRNA expression in WT mice. Conclusion: PPAR- seems to be needed for metabolic glucose homeostasis and anti-inflammatory effect of acute exercise. Its absence may induce over-expression of pro-inflammatory cytokines in LPS stimulus. Moreover, moderate exercise or PPAR- agonist did not reverse this response.
Keywords: acute exercise; cytokine; peritoneal macrophages; transcription factor